PROPERTY TERRORISM - CRIMINAL CRIMES PARTICIPANTS OF THE PARTICIPANTS (Journal of actual problems of jurisprudence, 2019)
The article carries out the importance of the role of be`s institute in protecting and keeping human values in traditional Kazakh society.